Acetaminophen Inhibits Intestinal P-Glycoprotein Transport Activity - Novak, Analia (2013)
Repeated acetaminophen (AP) administration modulates intestinal P-glycoprotein (P-gp) expression. Whether AP can modulate P-gp activity in a short-term fashion is unknown. We investigated the acute effect of AP on rat intestinal P-gp activity in vivo and in vitro. In everted intestinal sacs, AP inhibited serosal-mucosal transport of rhodamine 123 (R123), a prototypical P-gp substrate. R123 efflux plotted against R123 concentration adjusted well to a sigmoidal curve. Vmax decreased 50% in the presence of AP, with no modification in EC50, or slope, ruling out the possibility of inhibition to be competitive. Inhibition by AP was absent at 0°C, consistent with interference of the active transport of R123 by AP. Additionally, AP showed no effect on normal localization of P-gp at the apical membrane of the enterocyte and neither affected paracellular permeability. Consistent with absence of a competitive inhibition, two further strategies strongly suggested that AP is not a P-gp substrate. First, serosal-mucosal transport of AP was not affected by the classical P-gp inhibitors verapamil or Psc 833. Second, AP accumulation was not different between P-gp knock-down and wild-type HepG2 cells. In vivo intestinal absorption of digoxin, another substrate of P-gp, was assessed in the presence or absence of AP (100 μM). Portal digoxin concentration was increased by 214%, in average, by AP, as compared with digoxin alone. In conclusion, AP inhibited P-gp activity, increasing intestinal absorption of digoxin, a prototypical substrate. These results suggest that therapeutic efficacy of P-gp substrates can be altered if coadministered with AP.